Mystery—Whereof We Cannot Know, Yet Cannot Keep Silent - Tsun Haggarty, Holly; Karrow, Douglas D.; Harvey, Sharon R. (Journal of the Canadian Association for Curriculum Studies, 2025)
After the long labour of bringing a journal issue from idea to reality, an editorial gives the editors an opportunity to stand at the threshold and invite readers in. In this special issue, here’s what you will find: eight curriculum scholars, including the editors, wondering about “Mystery, World and Education”, as they ask themselves: What is mystery? How have I experienced it? What ways of knowing, teaching and/or learning does mystery suggest? This issue asserts no joint position. Rather, it tells eight unique stories, emerging from what the scholars are concerned about as educators, how and what they have learned from opening to mystery, and how this relates to their aspirations for curriculum. However, out of the diversity, commonalities emerge that speak to the nature of mystery. The scholars begin their inquiries wondering about mystery in terms of knowledge, qua the unknown and unknowable. Thinking about the unknowable is related to experiences of indeterminacy and enigma—mystery is found both in liminal spaces and as liminal. Significantly, the scholars experience mystery in and through their relations with more-thans—other persons, more-than-humans (animals, animate beings, agented things), Spirit Beings, Being itself and the Divine. Mystery develops from an epistemological to an existential concern. Theorizing mystery entails explicating one’s ontological (or metaphysical) beliefs. Come, tarry, experience what it is to dwell on, with and in mystery.